Are Chinese nationals' attitudes to wildlife tourist attractions different from those of other nationalities? - Moorhouse, TP; D'Cruze, N; Macdonald, D (Routledge, 2019)
Many wildlife tourist attractions (WTAs) have negative impacts on animal welfare and species conservation. In the absence of regulation, raising standards requires tourists to create market pressure by choosing to attend WTAs with benefits for wildlife. We surveyed respondents from five countries – China, Australia, Canada, UK and USA – to quantify how attitudes to captive animals, and towards WTAs’ outputs and standards, may vary with nationality. Our aim was to provide a firm basis for behaviour change interventions to alter current patterns of tourist consumption of WTAs. All respondents agreed on the importance of conservation and animal welfare, but Chinese respondents were twice as likely to believe that WTAs wouldn't be allowed to exist if they were bad for animals, and that WTAs' promotional materials were reliable indicators of welfare and conservation standards. These findings indicate Chinese respondents had fundamentally similar attitudes to those from the other countries, but differed in how those attitudes were likely to be applied. Chinese tourists may experience more barriers to aligning their actions with their values with respect to WTAs. Removing these barriers may require information campaigns to highlight the lack of regulation, and the unreliability of some WTAs’ promotional materials and tourists’ reviews.